Czynnik czasu w procesach decyzyjnych w organizacji - Staś, Lena (Time factor in the decision making process in the organization, 2006)
In conditions of frequent and profound changes quick action and decision making process become the core competency of executives. The author in the article tries to tentatively analyze the following problems: which phase of decision making process lasts the longest, do executives feel the need of change in their attitude and behaviour concerning rational time management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 48-52